Das políticas públicas de inclusão escolar à atuação do profissional de apoio/monitor - Fonseca, Manoela (2016)
The present study entitled “From the public policies of school inclusion to the practice of the supporting professional/monitor” aims at getting to know how the practice of the supporting professional/monitor occurs in the context of a private school in the city of Santa Maria. The investigation is characterized by the systemic thinking and the methodological approach follows the bricolage perspective. From authors like Vasconcellos (2013); Kincheloe and Berry (2009) – the assumption is that reality is built from the established relations. Larrosa‟s studies (2002) permeates the research movements and create experience networks. An analytical approach with the public policies of school inclusion from the theoretical background proposed by Maturana (2009), Maturana e Varela (2011), Meirieu (2002), Schlichting e Barcelos (2012), Carneiro (2015), Martins (2011) among others allowed a brief characterization in the practice of the support professional/monitor according to the legal documents. The private school network, as research location, was mapped through the statistics-educational data which were available in the National Institute of Educational Studies and Research – (INEP, abbreviation in Portuguese) – providing new opportunities of approaching. The context of the research took place in the school identified as “A”. The methodological tool used was a semi structured interview, and five supporting professionals/monitors and a special education teacher took part in it. In the perspective that the consensual spaces of language produce a shared reality, it was possible to analyze how the service of this professional has been happening in a school network which is poorly studied. Two wide axes conducted the analyses: opportunities for action; conceptions about the supporting professional/monitor in the school context. Considering all the evidence, it is important to highlight that the school prefers professionals connected to the field of special education in order to work with these supporting professionals/monitors, as well as an understanding that these ones must act pedagogically with students who are the target of Special Education enrolled in the regular school system. Among the practices, one of them is carrying out the Specialized Education Service, checking the planning and evaluations and carrying them out. The researched individuals acknowledge that their profession practice is beyond the specific functions of support and hygiene, locomotion and feeding, they take responsibilities which go beyond what is mentioned in the public policies of school inclusion. It is also observed that working as a supporting professional/monitor does not involve a regulated profession and it does not constitute a specific field of knowledge, however it does involve a role inside the school context, and that can be performed by professionals from different areas.